Hybrid Nanostructured Magnetite Nanoparticles: From Bio-Detection and Theragnostics to Regenerative Medicine - Yolanda Piñeiro (Magnetochemistry, 2020)
Nanotechnology offers the possibility of operating on the same scale length at which biological processes occur, allowing to interfere, manipulate or study cellular events in disease or healthy conditions. The development of hybrid nanostructured materials with a high degree of chemical control and complex engineered surface including biological targeting moieties, allows to specifically bind to a single type of molecule for specific detection, signaling or inactivation processes. Magnetite nanostructures with designed composition and properties are the ones that gather most of the designs as theragnostic agents for their versatility, biocompatibility, facile production and good magnetic performance for remote in vitro and in vivo for biomedical applications. Their superparamagnetic behavior below a critical size of 30 nm has allowed the development of magnetic resonance imaging contrast agents or magnetic hyperthermia nanoprobes approved for clinical uses, establishing an inflection point in the field of magnetite based theragnostic agents.